2015
DOI: 10.1039/c5cc07853a
|View full text |Cite|
|
Sign up to set email alerts
|

Oral delivery of a platinum anticancer drug using lipid assisted polymeric nanoparticles

Abstract: Self-assembled cholesterol-asplatin-incorporated nanoparticles (SCANs) were prepared for oral delivery of a Pt(IV) prodrug. SCANs exhibit high gastrointestinal stability, sustained drug release and enhanced cell uptake. The oral bioavailability of SCANs was 4.32-fold higher than that of free Pt(IV) prodrugs. The oral administration of SCANs efficaciously inhibits tumor growth with negligible toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…SCANs showed 4.32-fold higher oral bioavailability than that of free Pt(IV) prodrug and efficaciously inhibited tumor growth with negligible toxicity after oral administration. 34 Miller et al demonstrated that Pt(IV) prodrug-loaded PLGA-PEG NPs accumulated at high levels within tumor-associated macrophages (TAMs) after intravenous (i.v.) injection, and that TAMs served as a local drug depot, gradually releasing the Pt payload into neighboring tumor cells.…”
Section: Polymeric Npsmentioning
confidence: 99%
“…SCANs showed 4.32-fold higher oral bioavailability than that of free Pt(IV) prodrug and efficaciously inhibited tumor growth with negligible toxicity after oral administration. 34 Miller et al demonstrated that Pt(IV) prodrug-loaded PLGA-PEG NPs accumulated at high levels within tumor-associated macrophages (TAMs) after intravenous (i.v.) injection, and that TAMs served as a local drug depot, gradually releasing the Pt payload into neighboring tumor cells.…”
Section: Polymeric Npsmentioning
confidence: 99%
“…[5][6][7] Examples of metallated NPs include micellar metal-based MRI or SPECT/CT imaging agents, 8,9 and formulation NC-6004 or Nanoplatin™ (cisplatin encapsulated in micelles composed of PEG and poly(γ-benzyl-L-glutamate) (PEG-PGlu)), which is under phase I/II clinical evaluation for the treatment of pancreatic cancer. 10 The development of nanostructured materials functionalised with metal complexes as alternatives for administering anticancer metallodrugs is currently receiving attention with synthetic polymers, [11][12][13][14][15][16][17][18][19][20] however, little is known about the utilisation of natural polymers. Nanoparticles based on biopolymers, such as the cationic polysaccharide chitosan, have been demonstrated to possess various favourable features including those for drug and gene delivery, biosensing, therapy, and molecular imaging because of their excellent high biocompatibility, bio-degradation, hydrophilicity, and low toxicity toward mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up publication, this group also demonstrated in vivo properties of Asplatin using a self-assembled nanocarrier. 73 In this regard, Hey-Hawkins and coworkers also reported covalently linked conjugates of cisplatin and cyclooxegenase COX inhibitors which demonstrated similar mechanism of action after intracellular cleavage of the components (Figure 4A). 74 They used indomethacin or ibuprofen as the axial ligands.…”
Section: Activationmentioning
confidence: 81%